CONSTRUCT THE TRIPLE ZERO GRAPH OF RING Z_n USING PYTHON - Putri Wulandari; Vika Yugi Kurniawan; Nughthoh Arfawi Kurdhi (Barekeng)
Let  be a commutative ring with nonzero identity and  there exists  such that , , ,  denotes the set of all triple zero elements of . The triple zero graph of , denoted by , is an undirected graph with vertex set  where two distinct vertices  and  are adjacent if and only if , and there exists a nonzero element  of  such that , , and . Python is a programming language with simple and easy-to-learn code that can be used to solve problems in algebra and graphs. In this paper, we construct the triple zero graph of ring  using Python. Based on the output of the program, several properties of  are obtained, such as if  and , then  is a planar graph, if  with  is prime numbers, then  is a complete graph , and if  with  is prime numbers and , then  is a connected graph.